Адаптаційні реакції організму студенток із різною масою тіла в динаміці першого року навчання - Добростан, Оксана; Філімонова, Наталія; Плиска, Олександр; Dobrostan, Oksana; Filimonova, Natalay; Pluska, Oleksandr (Східноєвропейський національний університет імені Лесі Українки, 2016)
Для дослідження адаптаційних реакцій із студенток першого курсу НПУ ім. М. П. Драгоманова сформовано дві групи: І склали студентки з нормальною масою тіла, ІІ – студентки з надмірною масою тіла. Порівняльний аналіз показників варіабельності серцевого ритму студенток із різним ІМТ на кожному етапі дослідження виявив: починаючи з другого етапу, у студенток ІІ групи, порівняно з I, значуще менш виражений тонус ПВ ВНС, менш адекватне функцiонування серця, більша централізація управління серцевим ритмом. Результати наших досліджень указують на те, що в ІІ групі, порівняно з І, напруження регуляторних меха-нізмів було значуще більшим упродовж першого навчального року, а отже, «фізіологічна ціна адаптації» вища. A deviation in body weight from a norm is essential in situations which put high demands to a human body. Therefore, the purpose of our research was to study adaptive responses of students with different weight in the dynamics of the first year of study by analyzing the degree of tension of regulatory systems. For the researchit was formed two groups from the number of students of the first year of M.P. Drahomanov NPU: I group has been consisted by students with normal body weight, II – students are overweight. The dynamics of the academic year in the I group is set only a tendency to intension the compensatory-adaptive mechanisms, while in the II group is found significant tension compensatory-adaptive mechanisms since the second phase of the study. Detected changes of heart rate in the II group in the last stages of the research can be described as a transition from substantial intension of compensatory-adaptive mechanisms of the organism within the physiological norm to unstable adaptation. In addition, a comparative analysis of heart rate variability students with different BMI at each stage of the study showed: starting from the second stage of the II group of students in comparison with I one a tone of parasympathetic divisionis much less expressed, less adequate functioning of the heart, more centralizationof heart rhythm control. Consequently, in the II group in comparison withthe I group the intensionof regulatory mechanisms was significantly higher during the first academic year, and therefore «price physiological adaptation» higher. In such a way we can assume that students are overweight are ina risk group of psychosomatic diseases, which demands the implementation of individual approach and individual studying programs in some disciplines, and especially individual programs physical training lessons during the educational process.
Adaptation Responses of Student’s Organisms with Different Weight in the Dynamics of the First Year of Study.
Keywords: адаптація; студентки; ступінь напруження; регуляторні механізми; adaptation; the degree of stress; regulatory mechanisms; student